The phantom of the opera - Schumacher, Joel
The stage musical sensation magically and hauntingly comes to the screen in director Joel Schumacher's lavish production, sweeping audiences aloft to new cinematic heights of sight-and-sound grandeur. Gerard Butler (the Phantom), Emmy Rossum (winner of the National Board of Review Breakthrough Performance and Critics Choice Best Young Actress Awards as Christine) and Patrick Wilson (as Raoul) play the fateful love triangle that unfurls in splendor, suspense - and in the music of the night.